2021
DOI: 10.3390/ma14041004
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and Pozzolanic Properties of Biomass Ashes Generated by Wheat and Soybean Straw Combustion

Abstract: A sustainable use of locally available wastes from agriculture as supplementary cementitious materials (SCMs) is an alternative solution for the prevention of excessive raw material usage, reduction of CO2 emission and cost-effective concrete production. This paper studies the reactivity of non-traditional waste SCMs: Wheat straw ash (WSA), mixture of wheat and soybean straw ash (WSSA) and soybean straw ash (SSA), which are abundant as agricultural by-products in Serbia. The chemical evaluation using XRF techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Although biomass makes up 61% of the total potential of RES in Serbia, its usage rate for energy purposes is still not more than two percent. However, growing amounts of biomass ash are created as waste products during its combustion, estimated at five thousand tons per year [5,6]. They are most commonly disposed of in landfills or recycled on agricultural fields.…”
Section: Introductionmentioning
confidence: 99%
“…Although biomass makes up 61% of the total potential of RES in Serbia, its usage rate for energy purposes is still not more than two percent. However, growing amounts of biomass ash are created as waste products during its combustion, estimated at five thousand tons per year [5,6]. They are most commonly disposed of in landfills or recycled on agricultural fields.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been reported by [ 23 ], who found that mechanochemical activation improved the reactivity of the biomass fly ash, resulting in strength comparable to that of the reference for 5–15% cement replacement. The combination of mechanochemical activation with other treatments that have been reported to enhance the performance of biomass ash in cement-based materials, such as the removal of lightweight particles by floatation [ 29 ] and the addition of silica fume during the milling process [ 38 ], is worthy of further investigation for obtaining higher strength composites.…”
Section: Resultsmentioning
confidence: 99%
“…At these levels of substitution, the filling effect of the biomass ash, as well as its potential hydraulic and/or pozzolanic activity, has been found to counteract the dilution effect, resulting in adequate or enhanced strength performances. Pre-treatment of the biomass ash—including water washing [ 24 , 34 ], mechanical and chemical activation [ 23 , 38 ], heating, and removal of organic matter [ 29 ]—has been proven effective for improving the reactivity of the ash and thus the mechanical performance of biomass-ash-modified cementitious composites. It should be noted that the majority of the abovementioned studies concerned the utilization of BFA [ 18 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 31 , 33 , 34 , 35 ] in cement composites, and only a few focused on BBA [ 18 , 20 , 29 , 30 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have introduced agricultural wastes, in form of ash, as a partial replacement of cement or as an alkaline activator including rice husk ash (RHA) [1], olive waste ash (OWA) [2], sugar cane bagasse ash (SCBA) [3], corn cob ash (CCA) [4], palm oil fuel ash (POFA) [5], wheat straw ash (WSA) [6], soya straw ash (SSA) [7], almond shell ash (ASA) [8], cornstalk ash (CSA) [9], barley straw ash (BSA) [10], etc.…”
Section: Review On the Application Of Biomass Ashes In Masonry Mortarsmentioning
confidence: 99%